ADHD : evaluation and care (Pediatric collections., 2019)
"Attention-deficit/hyperactivity disorder (ADHD) is the most common behavioral condition and the second most common chronic illness in children. However, current objective assessments are of limited use in clarifying the diagnosis. This collection offers an evidence-based approach to evaluating children for ADHD. It also addresses treatment challenges, including prescribing practices for stimulant and nonstimulant ADHD medications, monitoring for medication adherence, side-effects, dosing, and medication adjustments. Additionally, discussion of the effectiveness of nonpharmacologic treatments such as neurofeedback, cognitive training, and herbal or dietary supplements is provided"--Publisher's description